Physical-chemical characterization of red table wines produced in the Planalto Norte region of Santa Catarina, harvest 2022 - Kowal, Alcemir Nabir; Schmidt, Eduarda; Maciel, Thalia Aparecida Silva; Almeida, Rabechlt Stange; Jansen, Thuany Aparecida Levandoski; Farias, Eduardo Virmond Souza; Steidel, Otávio Frederico Tschoeke; Palinguer, Rodrigo; Demetrio, Kelly Eduarda; Wisniewski, Caroline de Souza; et al. (Revista de Ciências Agroveterinárias, 2023)
The work was carried out with the objective of carrying out the physical-chemical characterization of red table wines produced in Planalto Norte Catarinense, harvest 2022, verifying the quality of these wines and their compliance with current Brazilian legislation. In all, twenty-four samples of red table wines were collected from the municipalities of Bela Vista do Toldo (2), Canoinhas (4), Ireneópolis (1), Itaiópolis (1), Mafra (2), Papanduva (2), Porto União (4), Rio Negrinho (3) and São Bento do Sul (5). During the month of August 2022, the physical-chemical characterization of the samples was carried out in the Fruit Growing Laboratory of the Federal Institute of Santa Catarina – Campus Canoinhas. Relative density, soluble solids, º Babo, total acidity, hydrogen potential (pH), color 420 nm, color 520 nm, color 620 nm, color tone, color intensity and total polyphenols were evaluated. The results for the evaluated variables were: total acidity (109.6 meq L-1), density (0.995), soluble solids (7.3 ºBrix), pH (3.32), staining 420 nm (2.707), staining 520 nm (4.961 nm), color 620 nm (0.812), color intensity (8.48), color hue (0.57) and total polyphenols (1049.8 mg L-1 gallic acid). The results observed in the present work demonstrate the potential of the Planalto Norte Catarinense region for the elaboration of red table wines, with the results, for the most part, in accordance with the current legislation. Regarding the results of the physical-chemical analyses, it was verified that there is a predominance of the elaboration of dry table wines. with lower coefficient of variation for these variables.